2009
DOI: 10.1021/es802163c
|View full text |Cite
|
Sign up to set email alerts
|

Trans-Pacific and Regional Atmospheric Transport of Polycyclic Aromatic Hydrocarbons and Pesticides in Biomass Burning Emissions to Western North America

Abstract: The trans-Pacific and regional North American atmospheric transport of polycyclic aromatic hydrocarbons (PAHs) and pesticides in biomass burning emissions was measured in air masses from April to September 2003 at two remote sites in western North America. Mary’s Peak Observatory (MPO) is located in Oregon’s Coast Range and Cheeka Peak Observatory (CPO) is located on the tip of the Olympic Peninsula in Washington State. During this time period, both remote sites were influenced by PAH and pesticide emissions f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(58 citation statements)
references
References 33 publications
3
54
0
Order By: Relevance
“…5, Bottom). For example, BaP emitted from East Asia travels thousands of miles over the Pacific Ocean, reaching the west coast of the United States, consistent with previous observational studies that identified trans-Pacific atmospheric transport of PAHs (34)(35)(36). Similarly, BaP emitted from Western Europe travels to the east, and BaP emitted from South Africa travels over the South Atlantic Ocean, reaching South America.…”
Section: Resultssupporting
confidence: 87%
“…5, Bottom). For example, BaP emitted from East Asia travels thousands of miles over the Pacific Ocean, reaching the west coast of the United States, consistent with previous observational studies that identified trans-Pacific atmospheric transport of PAHs (34)(35)(36). Similarly, BaP emitted from Western Europe travels to the east, and BaP emitted from South Africa travels over the South Atlantic Ocean, reaching South America.…”
Section: Resultssupporting
confidence: 87%
“…Further details on nest access, nestling and adult sampling, and transmitter attachment procedures were described previously. 23,24 Contaminant Analysis. (See Supporting Information for more detailed methods).…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…The region is dissected by a number of mountain ranges up to 4000 m altitude running north to south, and is the first landfall for pollutants transported atmospherically from the increasingly industrialized economies of Asia. 23 The osprey (Pandion haliaetus) is an obligate piscivore and a common breeding species on lakes and rivers across much of the globe. Ospreys integrate exposure from the entire food chain, and were selected here and elsewhere as effective sentinels of environmental contamination.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Approximately 20 g of sediment was mixed with sodium sulfate until the mixture was free-flowing. The sediment was extracted with 75:25 hexane:acetone using previously described PLE methods (Primbs et al, 2008;Genualdi et al, 2009). The extracts were further purified with silica solid phase extraction, and spiked with isotopically-labeled internal standards prior to GC/MS analysis.…”
Section: Sediment Extractionmentioning
confidence: 99%